CORPUS-BASED TRANSLATION STUDY ON THE SIMPLIFICATION OF CHINESE SUBTITLES IN ENGLISH-LANGUAGE FILMS - Su Tingting; Mohamed Abdou Moindjie; Manjet Kaur Mehar Singh (INTERNATIONAL JOURNAL OF MODERN EDUCATION (IJMOE), 2024)
While previous research has explored simplification in literary translation studies, this study’s focus on universals in audiovisual translation studies(AVT), especially in subtitling. In the era of advancing technology, where machine translation and automated translation analysis tools play a crucial role, the study of simplification as a universal phenomenon provides valuable insights. Understanding which translation features are universal across different language pairs can guide improvements in modern translation analysis tools and methods, and enhance translation accuracy. This study delves into the realm of translation studies to investigate simplification in Chinese subtitles of English-language films compared to Chinese subtitles of Chinese-language films. The research explores the presence of simplification in translation by examining three key aspects: lexical variety, lexical density, and high-frequency words. The findings reveal that Chinese subtitles of English-language film , as translated text, exhibit a reduced level of lexical variety when compared to Chinese subtitles of Chinese-language films, as the non-translations. Specifically, Chinese subtitles of English-language films employ more function words and fewer content words, resulting in lower lexical density than Chinese subtitles in Chinese-language films. The statistical analysis of high-frequency words further supports the notion that high-frequency words are used more frequently in translated Chinese subtitles than in the original Chinese subtitles. These results align with the simplification hypothesis proposed by Laviosa (1998) and Hu (2007). This research aims to enhance the comprehension of the intricacies of Chinese translation, not only across linguistic boundaries but also in the realm of technology, contributing to the reference of translation studies and practice.